O portal do Centro de Ciências Humanas, Letras e Artes da Universidade Federal da Paraíba: usuários e usabilidade - Silva Júnior, Laerte Pereira da (2012)
The Carta de Serviços ao Cidadão of the Universidade Federal da Paraíba aims at inform the citizens the services provided by this university. The Portal of the Centro de Ciências Humanas Letras e Artes (CCHLA) is part of the web information source indicated by such document. Thus, the present research intends to collaborate to the increasing of the quality in use of this source of information through the Study of Users in the Information Science area based on the Usability Engineering, mainly the concept of usability by Jakob Nielsen, associated to the attributes of: learning facility, use efficiency, memorizing facility, error occurrences and subject satisfaction. Besides, this research discusses the history of the Study of Users and its traditional, alternative and hybrid approaches, conceptualizes both the corporative websites and the Architecture of Information and characterizes the Usability. This descriptive quantitative qualitative research was developed with 471 students of the Social Science undergraduate course, and of the Sociology and Anthropology postgraduate courses, its sample was of 59 users. The data collection procedure was through online questionnaire put over the classrooms and other places in the CCHLA, including its homepage, in the websites of the given courses and of the Departamento de Ciências Sociais. The analysis of Usability of the CCHLA portal was done considering as reference the general and specific categories which evaluation resulted from the Likert scale related to the questionnaire response agreement criteria. The research revealed that the portal users were predominantly undergraduate students in their first year course in Social Science and experienced internet users who monthly access the portal to get information about the Departamento de Ciências Sociais. All the attributes have reached a good level average, which resulted in a good level of the users´ performance and satisfaction in the interaction with the portal. Therefore, the portal quality proved to be good facing the overall usability average being classified as good usability - 3.2 average in an interval of 0,0 to 5,0 points.